Preparation method of irradiation temperature-sensitive ruthenium-ethylenediamine tetraacetic acid imprinted polymer

The preparation of thermosensitive ruthenium-ethylenediaminetetraacetic acid blot polymers through RAFT polymerization solves the problem of low ruthenium separation and enrichment efficiency in secondary resources, and realizes efficient and environmentally friendly ruthenium resource recycling, providing a fast and low Cost process path.

CN119320478AActive Publication Date: 2025-01-17LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411416569.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-17
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The prior art has low separation and enrichment efficiency of ruthenium in secondary resources, long process flow, pollutes the environment, is difficult to industrially apply, and has poor selectivity of traditional methods.

Method used

The linear thermosensitive polymer polyN,N-diethylacrylamide was prepared by reversible addition-break chain transfer polymerization (RAFT) method, and then the thermosensitive block was synthesized with acrylamide, and finally irradiated by cobalt-60 The temperature-sensitive ruthenium-ethylenediaminetetraacetic acid complex was introduced by solution polymerization to form a thermosensitive ruthenium-ethylenediaminetetraacetic acid blot polymer.

Benefits of technology

It achieves rapid polymerization reaction at room temperature, improves production efficiency, no residue in the material, green and low energy consumption, short preparation time, stable material structure, fast adsorption rate of adsorbent, suitable for temperature regulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320478A_ABST
    Figure CN119320478A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an irradiation temperature-sensitive ruthenium-ethylenediamine tetraacetic acid imprinted polymer, which comprises the following steps: firstly, preparing a linear temperature-sensitive polymer poly N, N-diethylacrylamide by adopting reversible addition-fragmentation chain transfer polymerization; then, the poly N, N-diethylacrylamide is used as an RAFT (reversible addition-fragmentation chain transfer) reagent, and the poly N, N-diethylacrylamide and acrylamide are synthesized into a temperature-sensitive block; and finally, co-dissolving the thermo-sensitive block, acrylamide, acrylic acid, N, N-methylene bisacrylamide and a ruthenium-ethylenediamine tetraacetic acid complex in a methanol aqueous solution, and introducing the thermo-sensitive block through a cobalt-60 irradiation solution polymerization method, thereby obtaining the thermo-sensitive ruthenium-ethylenediamine tetraacetic acid complex imprinted polymer. The preparation method has the characteristics of short time, environmental protection and high production efficiency, and an adsorbent prepared from the obtained thermosensitive ruthenium-ethylenediamine tetraacetic acid imprinted polymer is relatively high in adsorption rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of precious metal recovery, and in particular to a method for preparing an irradiated temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer. Background Art

[0002] Ruthenium belongs to the platinum group elements and is the least abundant of the platinum group metals, with a content of only 10 -3 ppm. Due to its excellent physical and chemical properties, ruthenium is widely used in aerospace, chemical, electronic and pharmaceutical industries, and its demand and application scope are increasing year by year. However, my country's natural ruthenium ore reserves are very small and heavily dependent on imports. Therefore, in order to ensure the supply security of ruthenium raw materials in my country, it is of great strategic significance to study and expand the source of ruthenium.

[0003] Currently, the ruthenium content in secondary resources is much higher than that in primary resources. Therefore, recovering ruthenium from ruthenium-containing secondary resources can not only protect the environment, but also realize the recycling of ruthenium resources. However, the composition of the leaching solution of secondary resources is complex, and the traditional methods of separation and enrichment of ruthenium are generally poor in selectivity. Therefore, complicated pretreatment is required before separation and enrichment. This leads to problems such as low efficiency of existing technologies, long process flow, environmental pollution and difficulty in industrial application. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing an irradiation temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer with short time, environmental protection and high production efficiency.

[0005] In order to solve the above problems, the present invention discloses a method for preparing an irradiated temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer, which is characterized in that: the method first adopts reversible addition-fragmentation chain transfer polymerization (RAFT) to prepare a linear temperature-sensitive polymer poly (N,N-diethylacrylamide) (PDEA); then the poly (N,N-diethylacrylamide) (PDEA) is used as a RAFT agent and acrylamide (AM) to synthesize a temperature-sensitive block (PDEA-bP (DEA-co-AM)); finally, the temperature-sensitive block is co-dissolved with acrylamide, acrylic acid, N,N-methylenebisacrylamide and a ruthenium-ethylenediaminetetraacetic acid complex in a methanol aqueous solution, and the temperature-sensitive block is introduced by cobalt-60 irradiation solution polymerization to obtain a temperature-sensitive ruthenium-ethylenediaminetetraacetic acid complex imprinted polymer (Ru(III)-EDTA-TIIP).

[0006] The poly N,N-diethylacrylamide (PDEA) is prepared by the following method: azobisisobutyronitrile, 2-(dodecyl trithiocarbonate)-2-methylpropionic acid and N,N-diethylacrylamide are dissolved in excess ethyl acetate, mixed evenly, nitrogen with a purity of 99.999% is introduced for 15-20 minutes, and then sealed, and stirred in an oil bath at 60-80°C for reaction for 30-40 hours; after the reaction is completed, ethyl acetate is used as a solvent and n-hexane is used as a precipitant to perform three dissolutions and three precipitations on the reaction product to obtain PDEA; the molar ratio of the azobisisobutyronitrile, the 2-(dodecyl trithiocarbonate)-2-methylpropionic acid and the N,N-diethylacrylamide is 1: (15-25): (950-1050).

[0007] The temperature-sensitive block is prepared by the following method: azobisisobutyronitrile, poly N,N-diethylacrylamide (PDEA), acrylamide and N,N-diethylacrylamide are co-dissolved in excess N,N-dimethylformamide, mixed evenly, introduced with nitrogen gas with a purity of 99.999% for 15-20 minutes and then sealed, stirred in an oil bath at 60-80°C for reaction for 30-40 hours, three dissolutions and three precipitations are carried out with ethyl acetate as solvent and n-hexane as precipitant, and then vacuum dried to constant weight to obtain the obtained product; the molar ratio of the azobisisobutyronitrile, the poly N,N-diethylacrylamide (PDEA) and the acrylamide is 1:(15-25):(950-1050); the molar ratio of the N,N-diethylacrylamide to the acrylamide is 1:1.5-1:2.5.

[0008] The thermosensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer is prepared by the following method: the thermosensitive block, acrylamide, acrylic acid and ruthenium-ethylenediaminetetraacetic acid complex are co-dissolved in an excess methanol aqueous solution with a volume ratio of 2:1, and after self-assembly in a water bath environment at 30-35°C for 1-2 hours, a cross-linking agent N,N-methylenebisacrylamide is added, and nitrogen with a purity of 99.999% is introduced for 15-20 minutes and then sealed; then, the mixture is heated at 30-40°C at 8KGy / h The irradiation dose is irradiated with cobalt-60 to initiate polymerization for 5 hours, and after the polymerization is completed, it is vacuum dried to constant weight to obtain; the mass ratio of the temperature-sensitive block to the acrylic acid is 1:5-1:20; the molar ratio of the acrylamide to the acrylic acid is 1:2-2:1; the molar ratio of the acrylic acid to the N,N-methylenebisacrylamide is 1:5-1:7; the added amount of the ruthenium-ethylenediaminetetraacetic acid complex accounts for 3.6%-11% of the molar amount of the acrylic acid.

[0009] An adsorbent is prepared by using the temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer prepared by the method described above.

[0010] The preparation method of an adsorbent as described above is characterized in that: the method refers to crushing the temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer, placing the particles after passing through a 30-120 mesh sieve into a 500 mesh filter bag, and placing it in a Soxhlet extractor to elute the ruthenium-ethylenediaminetetraacetic acid complex with analytically pure anhydrous ethanol as an eluent, and using ICP-AES to determine the concentration of the corresponding ruthenium-ethylenediaminetetraacetic acid complex in the etching solution. When the test value is lower than 0.02 μg / mL, the elution is stopped, and then the filter bag is alternately rinsed with methanol and water until the solution is neutral, and then vacuum dried to constant weight to obtain the adsorbent.

[0011] Compared with the prior art, the present invention has the following advantages: 1. The present invention adopts cobalt-60 irradiation field irradiation polymerization to prepare imprinted polymers, so that it can be carried out at room temperature or near room temperature. High-energy rays can quickly initiate the polymerization reaction, so that the irradiation polymerization can be completed in a short time, thereby improving production efficiency. In addition, irradiation polymerization does not require the addition of chemical initiators, and the obtained materials have no residues, so that the entire process has the advantages of being green, low energy consumption and low cost.

[0012] 2. The preparation time of the present invention is short and environmentally friendly, and the obtained temperature-sensitive ruthenium imprinted polymer has the characteristics of stable structure.

[0013] 3. The adsorbent prepared by the thermosensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer of the present invention has a faster adsorption rate. Due to the introduction of the thermosensitive block [poly (N,N-diethylacrylamide-g-poly (N,N-diethylacrylamide-g-acrylamide)], when the external ambient temperature changes, the thermosensitive block undergoes a sol / gel phase transition and causes the imprinted pores to change, thereby achieving a high level of adsorption and desorption by adjusting the temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0015] Figure 1 It is a preparation flow chart of the present invention.

[0016] Figure 2 This is a physical picture of the temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer prepared in Example 1 of the present invention.

[0017] Figure 3 The SEM images of the temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer (left picture) and the non-imprinted polymer (right picture) prepared in Example 1 of the present invention are shown.

[0018] Figure 4 This is a graph showing the adsorption performance of adsorbent A obtained in Example 1 of the present invention changing with time at different temperatures.

[0019] Figure 5 This is a graph showing the desorption performance of adsorbent A obtained in Example 1 of the present invention changing with time at different temperatures after adsorption.

[0020] Figure 6 This is a graph showing the reusability of adsorbent A obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] like Figure 1 As shown, a method for preparing an irradiated thermosensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer is firstly prepared by reversible addition-fragmentation chain transfer polymerization (RAFT) as a linear thermosensitive polymer poly N, N-diethylacrylamide (PDEA); then poly N, N-diethylacrylamide (PDEA) is used as a RAFT agent to synthesize a thermosensitive block (PDEA-bP(DEA-co-AM)) with acrylamide (AM); finally, the thermosensitive block is co-dissolved with acrylamide, acrylic acid, N, N-methylenebisacrylamide and ruthenium-ethylenediaminetetraacetic acid complex in a methanol aqueous solution, and the thermosensitive block is introduced by cobalt-60 irradiation solution polymerization to obtain a thermosensitive ruthenium-ethylenediaminetetraacetic acid complex imprinted polymer (Ru(III)-EDTA-TIIP). The specific process is as follows: Poly (N,N-diethylacrylamide) (PDEA) is prepared by the following method: azobisisobutyronitrile, 2-(dodecyl trithiocarbonate)-2-methylpropionic acid and N,N-diethylacrylamide are dissolved in excess ethyl acetate, mixed evenly, nitrogen with a purity of 99.999% is introduced for 15-20 minutes, sealed, stirred in an oil bath at 60-80°C for 30-40 hours; after the reaction is completed, ethyl acetate is used as a solvent and n-hexane is used as a precipitant to perform three dissolutions and three precipitations on the reaction product to obtain PDEA. The molar ratio of azobisisobutyronitrile, 2-(dodecyl trithiocarbonate)-2-methylpropionic acid and N,N-diethylacrylamide is 1:(15-25):(950-1050), preferably 1:20:1000.

[0022] The temperature-sensitive block [poly (N,N-diethylacrylamide-g-poly (N,N-diethylacrylamide-g-acrylamide), PDEA-bP (DEA-co-AM)] was prepared by the following method: azobisisobutyronitrile, poly (N,N-diethylacrylamide (PDEA), acrylamide and N,N-diethylacrylamide) were co-dissolved in excess N,N-dimethylformamide, mixed evenly, introduced nitrogen with a purity of 99.999% for 15-20 minutes and then sealed, stirred in an oil bath at 60-80°C for 30-40 hours, dissolved and precipitated three times with ethyl acetate as solvent and n-hexane as precipitant, and then vacuum dried to constant weight to obtain the obtained block. The molar ratio of azobisisobutyronitrile, poly N,N-diethylacrylamide (PDEA) and acrylamide is 1:(15-25):(950-1050), preferably 1:20:1000; the molar ratio of N,N-diethylacrylamide to acrylamide is 1:1.5-1:2.5, preferably 1:2.

[0023] Thermosensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer (Ru(III)-EDTA-TIIP) was prepared by the following method: the thermosensitive block, acrylamide, acrylic acid and ruthenium-ethylenediaminetetraacetic acid complex were co-dissolved in an excess methanol aqueous solution with a volume ratio (ml / ml) of 2:1, and after self-assembly in a water bath environment at 30~35°C for 1~2h, a cross-linking agent N,N-methylenebisacrylamide was added, and nitrogen with a purity of 99.999% was introduced for 15~20min and then sealed; then, polymerization was initiated by cobalt-60 irradiation at 30~40°C and an irradiation dose of 8KGy / h for 5h, and after the polymerization was completed, vacuum drying was performed to constant weight to obtain the obtained product. The mass ratio (g / g) of the thermosensitive block to acrylic acid is 1:5~1:20; the molar ratio of acrylamide to acrylic acid is 1:2~2:1; the molar ratio of acrylic acid to N,N-methylenebisacrylamide is 1:5~1:7; and the added amount of the ruthenium-ethylenediaminetetraacetic acid complex accounts for 3.6%~11% of the molar amount of acrylic acid.

[0024] The ruthenium-ethylenediaminetetraacetic acid complex, i.e., the template ion, is prepared according to the method disclosed in ZL 201810386065.2.

[0025] An adsorbent prepared by using a thermosensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer, and its preparation method: The thermosensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer was crushed, and the particles after passing through a 30-120 mesh sieve were placed in a 500 mesh filter bag, and placed in a Soxhlet extractor to elute the ruthenium-ethylenediaminetetraacetic acid complex with analytically pure anhydrous ethanol as an eluent, and the corresponding ruthenium-ethylenediaminetetraacetic acid complex concentration in the etching solution was determined by ICP-AES. When the test value was lower than 0.02 μg / mL, the elution was stopped, and then the filter bag was alternately rinsed with methanol and water until the solution was neutral, and vacuum dried to constant weight to obtain the adsorbent.

[0026] Example 1 Weigh 0.006g of azobisisobutyronitrile, 0.258g of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid (RAFT agent) and 4.54g of N,N-diethylacrylamide (DEA), dissolve them completely in a 25mL test tube with 9.423g of ethyl acetate, mix them evenly, pass 99.999% pure nitrogen gas at room temperature for 20 minutes, seal them, and stir them in a 70℃ oil bath for 36 hours. After the reaction is completed, use ethyl acetate as solvent and n-hexane as precipitant to dissolve and precipitate the initial product three times to obtain poly N,N-diethylacrylamide (PDEA).

[0027] 0.003g of azobisisobutyronitrile, 1.3104g of poly N,N-diethylacrylamide (PDEA) and 0.6486g of acrylamide were weighed and completely dissolved in a 25mL test tube with 2.6804g of N,N-dimethylformamide, and then 0.4972g of N,N-diethylacrylamide (DEA) was added and mixed evenly. After nitrogen with a purity of 99.999% was introduced at room temperature for 20min, the mixture was sealed and stirred in an oil bath at 70℃ for 36h. A mixed solvent of ethyl acetate and n-hexane with a volume ratio of 1:4 was used as a precipitant, and three dissolutions and three precipitations were performed. Subsequently, the mixture was placed in a vacuum oven at 40℃ until constant weight was obtained to obtain a thermosensitive block [poly N,N-diethylacrylamide-g-poly(N,N-diethylacrylamide-g-acrylamide)], PDEA-bP(DEA-co-AM).

[0028] Weigh 0.1g of thermosensitive block, 0.56g of acrylamide, 0.5g of acrylic acid and 0.2g of ruthenium-ethylenediaminetetraacetic acid complex and dissolve them in a mixed solvent of water and methanol with a volume ratio of 1:2. Self-assemble for 2h in a constant temperature water bath at 35°C and a magnetic stirring speed of 150 r / min. Add 6g of N,N-methylenebisacrylamide and stir until completely dissolved. Pass 99.999% pure nitrogen at room temperature for 20min and then seal to form a solution system. After irradiation polymerization with cobalt-60 for 5h, take out and place in a vacuum drying oven to dry to constant weight to obtain a thermosensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer (Ru(III)-EDTA-TIIP), such as Figure 2 shown.

[0029] The preparation of nonionic imprinted polymer (Ru(III)-EDTA-TINP) was the same as above except that the ruthenium-ethylenediaminetetraacetic acid complex was not added.

[0030] The obtained thermosensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer (Ru(III)-EDTA-TIIP) and non-imprinted polymer (Ru(III)-EDTA-TINP) were scanned by electron microscope. Figure 3 As shown. It can be observed from the figure that there are many holes on the surface of Ru(III)-EDTA-TIIP, and the holes are distributed relatively loosely. However, there are no obvious holes on the surface of Ru(III)-EDTA-TINP, and the stacking is dense. On the one hand, this morphological difference is due to the change in the interaction between the polymer microparticle interface caused by the self-assembly between the ruthenium-ethylenediaminetetraacetic acid complex and the functional monomer. At the same time, due to the hydrogen bonding between the functional monomer and the ruthenium-ethylenediaminetetraacetic acid complex in Ru(III)-EDTA-TIIP, the hydrogen bonding between the polymer molecular chains is weakened, resulting in a decrease in the interaction between the polymer and the solvent, making phase separation easier, so there are more holes and the surface is looser.

[0031] The dried Ru(III)-EDTA-TIIP was crushed by a pulverizer, and the particles of 30-120 mesh were sieved with a sieve and stored, and then placed in a 500-mesh filter bag (7.6×50 mm), and placed in a Soxhlet extractor to elute the ruthenium-ethylenediaminetetraacetic acid complex with anhydrous ethanol, and the corresponding ruthenium-ethylenediaminetetraacetic acid complex concentration in the etching solution was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) analysis technology. When the test value was lower than 0.02 μg / mL, the elution was stopped, and then the filter bag was alternately rinsed with methanol and water until the solution was neutral, and then placed at 45°C and vacuum dried to constant weight. After drying, adsorbent A was obtained.

[0032] Figure 4 The adsorption kinetic curves of Ru(III)-EDTA ions by adsorbent A at 25℃, 35℃ and 45℃ are shown in the figure. Compared with 25℃ and 45℃, Ru(III)-EDTA-TIIP has a higher adsorption amount at 35℃, which is due to the introduction of the thermosensitive block, which keeps the imprinted pores complete during the self-assembly of GIS-SIIP at 35℃; when the external temperature changes, the thermosensitive block undergoes a sol / gel phase transition, causing the expansion and contraction of the imprinted pores, which reduces the adsorption amount.

[0033] Figure 5The desorption amount of Ru(III)-EDTA over time after adsorption by adsorbent A. The figure shows that compared with 35℃ and 45℃, Ru(III)-EDTA-TIIP has a higher desorption amount at 25℃. When the adsorption temperature T=25℃ (lower than the LCST of the thermosensitive block), the molecular chain is in a stretched state, making the imprinted pores in a relaxed state, the integrity of the imprinted pores deteriorate, the spatial fit between the imprinted pores and the target ions deteriorate, the imprinted sites are incomplete imprinted sites, and the affinity of the imprinted pores for the ruthenium-ethylenediaminetetraacetic acid complex is weakened, so the adsorbed ruthenium-ethylenediaminetetraacetic acid complex is easily desorbed.

[0034] The synthesis method of Ru(III)-EDTA is as follows: add RuCl3 to EDTA, and the molar ratio of the two is 1:1. After complete dissolution, heat in a water bath at 60°C under magnetic stirring, react for 2 hours by condensation reflux, precipitate with 90% alcohol, filter to obtain a precipitate, and then vacuum dry the product in a drying oven at 60°C for 24 hours.

[0035] Take the same volume of Ru(III)-EDTA solution with a molar concentration of 0.013mmol / L, and use an inductively coupled plasma mass spectrometer (ICP-MS) to determine the ion concentration in the solution before adsorption. Take 0.1g of adsorbent A and adsorb it at 35℃ for 120min, then put it into 1% NH3•H2O solution and desorb it at 25℃ for 300min; repeat the adsorption-desorption cycle 12 times, and use an inductively coupled plasma mass spectrometer (ICP-MS) to determine the ion concentration after adsorption and after desorption. The results are as follows: Figure 6 As shown in the figure, after 8 adsorption-desorption cycles, the adsorption amount does not change much from the original value, indicating that the temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer prepared by the preparation method of the present invention has good reusability.

[0036] Example 2 Weigh 0.002g of azobisisobutyronitrile, 0.086g of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid (RAFT agent) and 1.513g of N,N-diethylacrylamide (DEA), dissolve them completely in a 25mL test tube with 3.141g of ethyl acetate, mix them evenly, pass 99.999% pure nitrogen gas at room temperature for 20 minutes, seal them, and stir them in a 70℃ oil bath for 36 hours. After the reaction is completed, use ethyl acetate as solvent and n-hexane as precipitant to dissolve and precipitate the initial product three times to obtain poly N,N-diethylacrylamide (PDEA).

[0037] 0.006g of azobisisobutyronitrile, 2.621g of poly N,N-diethylacrylamide (PDEA) and 1.2972g of acrylamide were weighed and completely dissolved in a 25mL test tube with 5.3608g of N,N-dimethylformamide, and then 0.9944g of N,N-diethylacrylamide (DEA) was added and mixed evenly. After nitrogen with a purity of 99.999% was introduced at room temperature for 20 minutes, the mixture was sealed and stirred in an oil bath at 70°C for 36 hours. A mixed solvent of ethyl acetate and n-hexane with a volume ratio of 1:4 was used as a precipitant, and three dissolutions and three precipitations were performed. Subsequently, the mixture was placed in a vacuum oven at 40°C until constant weight was obtained to obtain a temperature-sensitive block [poly N,N-diethylacrylamide-g-poly(N,N-diethylacrylamide-g-acrylamide)], PDEA-bP(DEA-co-AM).

[0038] 0.05g of thermosensitive block, 0.56g of acrylamide, 1.0g of acrylic acid and 0.3g of ruthenium-ethylenediaminetetraacetic acid complex were weighed and dissolved in a mixed solvent of water and methanol with a volume ratio of 1:2. Self-assembly was performed for 2h in a constant temperature water bath at 35°C and a magnetic stirring speed of 150 r / min. 7g of N,N-methylenebisacrylamide was added and stirred until completely dissolved. Nitrogen with a purity of 99.999% was introduced at room temperature for 20min and then sealed to form a solution system. After irradiation polymerization with cobalt-60 for 5h, the mixture was taken out and placed in a vacuum drying oven to be dried to constant weight to obtain a thermosensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer (Ru(III)-EDTA-TIIP).

[0039] The dried Ru(III)-EDTA-TIIP was crushed by a multifunctional pulverizer, and the particles of 30-120 mesh were sieved with a sieve and stored, and then put into a 500-mesh filter bag (7.6×50 mm), and placed in a Soxhlet extractor to elute the ruthenium-ethylenediaminetetraacetic acid complex with anhydrous ethanol, and the concentration of the corresponding ruthenium-ethylenediaminetetraacetic acid complex in the etching solution was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) analysis technology. When the test value was lower than 0.02 μg / mL, the elution was stopped, and then the filter bag was alternately rinsed with methanol and water until the solution was neutral, and then placed at 45°C and vacuum dried to constant weight. After drying, adsorbent B was obtained.

[0040] Example 3 Weigh 0.004g of azobisisobutyronitrile, 0.172g of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid (RAFT agent) and 3.027g of N,N-diethylacrylamide (DEA), dissolve them completely in a 25mL test tube with 6.282g of ethyl acetate, mix them evenly, pass 99.999% pure nitrogen gas at room temperature for 20 minutes, seal them, and stir them in a 70℃ oil bath for 36 hours. After the reaction is completed, use ethyl acetate as solvent and n-hexane as precipitant to dissolve and precipitate the initial product three times to obtain poly N,N-diethylacrylamide (PDEA).

[0041] 0.005 g of azobisisobutyronitrile, 2.184 g of poly N, N-diethylacrylamide (PDEA) and 1.081 g of acrylamide were weighed and completely dissolved in a 25 mL test tube with 4.4673 g of N, N-dimethylformamide, and then 0.8287 g of N, N-diethylacrylamide (DEA) was added and mixed evenly. After nitrogen with a purity of 99.999% was introduced at room temperature for 20 min, the mixture was sealed and stirred in an oil bath at 70 ° C for 36 h. A mixed solvent of ethyl acetate and n-hexane with a volume ratio of 1:4 was used as a precipitant, and three dissolutions and three precipitations were performed. Subsequently, the mixture was placed in a vacuum oven at 40 ° C until constant weight was obtained, and the temperature-sensitive block [poly N, N-diethylacrylamide-g-poly (N, N-diethylacrylamide-g-acrylamide)] was obtained, which was recorded as PDEA-bP (DEA-co-AM).

[0042] 0.05g of thermosensitive block, 1.12g of acrylamide, 0.5g of acrylic acid and 0.1g of ruthenium-ethylenediaminetetraacetic acid complex were weighed and dissolved in a mixed solvent of water and methanol with a volume ratio of 1:2. Self-assembly was performed for 2h in a constant temperature water bath at 35°C and a magnetic stirring speed of 150 r / min. 5.5g of N,N-methylenebisacrylamide was added and stirred until completely dissolved. Nitrogen with a purity of 99.999% was introduced at room temperature for 20min and then sealed to form a solution system. After irradiation polymerization with cobalt-60 for 5h, the mixture was taken out and placed in a vacuum drying oven to be dried to constant weight to obtain a thermosensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer (Ru(III)-EDTA-TIIP).

[0043] The dried Ru(III)-EDTA-TIIP was crushed by a multifunctional pulverizer, and the particles of 30-120 mesh were sieved with a sieve and stored, and then put into a 500-mesh filter bag (7.6×50 mm), and placed in a Soxhlet extractor to elute the ruthenium-ethylenediaminetetraacetic acid complex with anhydrous ethanol, and the corresponding ruthenium-ethylenediaminetetraacetic acid complex concentration in the etching solution was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) analysis technology. When the test value was lower than 0.02 μg / mL, the elution was stopped, and then the filter bag was alternately rinsed with methanol and water until the solution was neutral, and then placed at 45°C and vacuum dried to constant weight. After drying, adsorbent C was obtained.

Claims

1. A method for preparing an irradiation temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer, characterized in that: The method firstly adopts reversible addition-fragmentation chain transfer polymerization to prepare a linear thermosensitive polymer poly (N,N-diethylacrylamide); then the poly (N,N-diethylacrylamide) is used as a RAFT agent to synthesize a thermosensitive block with acrylamide; finally, the thermosensitive block is co-dissolved in a methanol aqueous solution with acrylamide, acrylic acid, N,N-methylenebisacrylamide and a ruthenium-ethylenediaminetetraacetic acid complex, and the thermosensitive block is introduced by a cobalt-60 irradiated solution polymerization method to obtain a thermosensitive ruthenium-ethylenediaminetetraacetic acid complex imprinted polymer.

2. The method for preparing an irradiation temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer according to claim 1, characterized in that: The poly N,N-diethylacrylamide is prepared by the following method: azobisisobutyronitrile, 2-(dodecyl trithiocarbonate)-2-methylpropionic acid and N,N-diethylacrylamide are dissolved in excess ethyl acetate, mixed evenly, nitrogen with a purity of 99.999% is introduced for 15-20 minutes, then sealed, and stirred in an oil bath at 60-80°C for reaction for 30-40 hours; after the reaction is completed, ethyl acetate is used as a solvent and n-hexane is used as a precipitant to perform three dissolutions and three precipitations on the reaction product to obtain the poly N,N-diethylacrylamide; the molar ratio of the azobisisobutyronitrile, the 2-(dodecyl trithiocarbonate)-2-methylpropionic acid and the N,N-diethylacrylamide is 1:(15-25):(950-1050).

3. The method for preparing an irradiation temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer according to claim 1, characterized in that: The temperature-sensitive block is prepared by the following method: azobisisobutyronitrile, poly N,N-diethylacrylamide, acrylamide and N,N-diethylacrylamide are co-dissolved in excess N,N-dimethylformamide, mixed evenly, nitrogen with a purity of 99.999% is introduced for 15-20 minutes and then sealed, stirred in an oil bath at 60-80°C for reaction for 30-40 hours, three dissolutions and three precipitations are carried out with ethyl acetate as solvent and n-hexane as precipitant, and then vacuum dried to constant weight to obtain the temperature-sensitive block; the molar ratio of the azobisisobutyronitrile, the poly N,N-diethylacrylamide and the acrylamide is 1:(15-25):(950-1050); the molar ratio of the N,N-diethylacrylamide to the acrylamide is 1:1.5-1:2.

5.

4. The method for preparing an irradiation temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer according to claim 1, characterized in that: The thermosensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer is prepared by the following method: the thermosensitive block, acrylamide, acrylic acid and ruthenium-ethylenediaminetetraacetic acid complex are co-dissolved in an excess methanol aqueous solution with a volume ratio of 2:1, and after self-assembly in a water bath environment at 30-35°C for 1-2 hours, a cross-linking agent N,N-methylenebisacrylamide is added, and nitrogen with a purity of 99.999% is introduced for 15-20 minutes and then sealed; then, the mixture is heated at 30-40°C at 8KGy / h. The irradiation dose is irradiated with cobalt-60 to initiate polymerization for 5 hours, and after the polymerization is completed, it is vacuum dried to constant weight to obtain; the mass ratio of the temperature-sensitive block to the acrylic acid is 1:5-1:20; the molar ratio of the acrylamide to the acrylic acid is 1:2-2:1; the molar ratio of the acrylic acid to the N,N-methylenebisacrylamide is 1:5-1:7; the added amount of the ruthenium-ethylenediaminetetraacetic acid complex accounts for 3.6%-11% of the molar amount of the acrylic acid.

5. An adsorbent prepared by using the temperature-sensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer obtained by the method as claimed in claim 1.

6. The method for preparing an adsorbent according to claim 5, characterized in that: The method comprises crushing the thermosensitive ruthenium-ethylenediaminetetraacetic acid imprinted polymer, placing the particles after passing through a 30-120 mesh sieve into a 500 mesh filter bag, placing the particles in a Soxhlet extractor, using analytically pure anhydrous ethanol as an eluent to elute the ruthenium-ethylenediaminetetraacetic acid complex, and using ICP-AES to determine the concentration of the corresponding ruthenium-ethylenediaminetetraacetic acid complex in the etching solution. When the test value is lower than 0.02 μg / mL, the elution is stopped, and then the filter bag is alternately rinsed with methanol and water until the solution is neutral, and vacuum dried to constant weight to obtain the adsorbent.

Citation Information

Patent Citations

  • Method for wet flue gas denitrification by ruthenium complexing agent

    CN108654310A

  • Thermo-sensitive ionic imprinting polymer for separating high rhenium acid radical ions and preparation method and application of thermo-sensitive ionic imprinting polymer

    CN110343222A

  • Preparation method of temperature-sensitive porous imprinted polymer

    CN113354781A

  • Synthesis of ion imprinted polymer particles

    WO2005063382A1